Artist or Imposter! Breaking the Barriers and ‘dancing’ the Data - Dianna Moodley; Clare Craighead (AOSIS, 2025)
This scholarly book aims to provoke a conscience-inducing disruption in arts teaching and learning practices within South African higher education. It advocates for a critical, humanising and compassionate pedagogy that responds to the daunting domestic realities faced by students – realities that were further intensified by the coronavirus disease 2019 (COVID-19) pandemic and subsequent lockdowns. Through emancipatory pedagogy and arts-based methodologies, this book empowers research participants as co-researchers, granting them the capacity to create and share knowledge in contexts where their voices are often marginalised. Employing an autoethnographic methodology that utilises reflective–reflexive, arts-based approaches, Artist or Imposter! Breaking the barriers and ‘dancing'the data explores art forms with humanising impulses as pedagogical interventions, opening fertile pathways toward embodied and empowering learning. It makes theoretical and epistemological contributions to new understandings of social constructivism in higher education, reframing pedagogy as a form of crisis-driven activism. In doing so, the authors invite open engagement with non-traditional and transdisciplinary methodologies, while also offering practical insights to strengthen higher education practices to support student well-being and academic success. Challenging the guardianship of ‘unadulterated'scientific research and rigid notions of disciplinary integrity, this book traverses methodological confines, defying and transcending dictated boundaries. It foregrounds stereotypical negativity around preconceived notions of epistemological paradigms and their constraining effect on research communities. By exposing how an overemphasis on epistemology can stunt intellectual freedom, the authors argue for more transformative research practices, where embodied practice and collaborative knowledge production provide new ways of understanding and navigating students'lived experiences. This book will be especially relevant for scholars and researchers in higher education, critical pedagogy and the humanities. Its unique combination of theoretical depth, methodological innovation and practical insight makes it especially relevant for academics seeking to rethink established paradigms, expand their methodological repertoire, and engage in scholarship that responds directly to the challenges of student well-being, equity and transformation.